2013
DOI: 10.1371/journal.pone.0073373
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Cultural Adaptations of Interventions Aimed at Smoking Cessation, Diet, and/or Physical Activity in Ethnic Minorities. A Systematic Review

Abstract: BackgroundThe importance of cultural adaptations in behavioral interventions targeting ethnic minorities in high-income societies is widely recognized. Little is known, however, about the effectiveness of specific cultural adaptations in such interventions.AimTo systematically review the effectiveness of specific cultural adaptations in interventions that target smoking cessation, diet, and/or physical activity and to explore features of such adaptations that may account for their effectiveness.MethodsSystemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
115
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(124 citation statements)
references
References 32 publications
(97 reference statements)
3
115
2
4
Order By: Relevance
“…66 For example, a cessation trial 67 reported no additional benefit to culturally tailored intervention materials compared to non-tailored materials among Blacks using NRT. Given findings in this sample and other samples of PLWH, 57 interventions that specifically target adherence to NRT or pharmacotherapy may be critical to yield better cessation rates.…”
Section: Discussionmentioning
confidence: 99%
“…66 For example, a cessation trial 67 reported no additional benefit to culturally tailored intervention materials compared to non-tailored materials among Blacks using NRT. Given findings in this sample and other samples of PLWH, 57 interventions that specifically target adherence to NRT or pharmacotherapy may be critical to yield better cessation rates.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of evidence supports this approach to tailor programs for specific communities, ethnicities, or cultures and warrants investigation in the area of BAM (28)(29)(30). Such work is particularly important given racial and ethnic disparities in health and health care across a wide range of disease categories influenced by stress (16).…”
Section: Introductionmentioning
confidence: 99%
“…113, 114). Although recent systematic reviews tested the persuasive effects of narratives (Braddock & Dillard, 2016;De Graaf, Sanders, & Hoeken, 2016) and other systematic reviews evaluated the effectiveness of behavioral interventions with culturally adapted strategies (Kong, Tussing-Humphreys, Odoms-Young, Stolley, & Fitzgibbon, 2014;Nierkens et al, 2013), only a few empirical studies have actually evaluated the effects that educational narratives that are culturally targeted to one group may have on other cultural groups (see for example Murphy et al, 2015, who explored the effects of a cervical cancer film developed for Mexican Americans on other ethnic groups). To our knowledge, for fotonovelas, such effects have not yet been studied empirically at all.…”
Section: Introductionmentioning
confidence: 99%